Financing new ventures : an entrepreneur's guide to business angel investment - Gregson, Geoffrey. (2013 digital library., 2014)
This book provides guidance on what makes a new venture more likely to attract external financing, with an emphasis on business angel investment. The author incorporates the views of business angels, venture capitalists, entrepreneurs, and legal advisors; draws upon the latest academic thinking on financing new ventures; and provides comparisons between business angel and venture capital investing to further inform the reader. The concepts, principles, and guidelines presented here will be relevant to entrepreneurs and investors, business support agencies, business students, and others interested in raising external investment and in developing an "investable" business.